Respon Pertumbuhan Bibit Tanaman Tebu (Saccharum officinarum L.) Pada Lama Perendaman Bahan Setek dalam Larutan ZPT Atonik: Sugarcane Seed Growth Response (Saccharum officinarum L.) on the duration of immersion of cuttings in atonic Zpt solution - Bambang Purwanto; Reka Wahyuni; Ansyori Ansyori (Politeknik Negeri Lampung, 2022)
One of the causes of low sugar production is the quality of sugar cane seeds. Seed quality is one of the factors that determine the success of sugarcane cultivation. Breeding bud chips is a vegetative sugarcane seedling using one-eye cuttings. In addition to nutrients, growth and seed quality are also influenced by growth regulators (ZPT). Atonic (auxin) is able to increase the metabolic rate so that cell development increases and the absorption area of ​​leaves is more which affects the increase in leaf area, and stimulates plant root growth, increasing root absorption of nutrients. The purpose of the study was to determine the growth response of sugarcane seedlings (Saccharum officinarum L.) on the duration of immersion of cuttings in Atonic PGR solution. The study was carried out using a randomized block design with 4 replications, and 6 levels of immersion time of sugarcane cuttings in Atonik PGR solution: P0 = control, P1 = 10 minutes, P2 = 20 minutes, P3 = 30 minutes, P4 = 40 minutes, and P5 = 50 minutes. Testing the data with an orthogonal polynomial test. Research conclusions: (1) For every 10 minutes of immersion time of sugarcane cuttings in Atonic PGR solution: (a) the length of the sugarcane seeds increased by 0.379 cm, and (b) the dry weight of the sugarcane seeds increased by 0.007 g. (2) The duration of immersion of sugarcane cuttings of one bud in Atonic ZPT solution did not show any effect on the percentage of budding cuttings of sugarcane cuttings, the number of leaves, stem diameter, and wet weight of seedlings. Keywords: Sugarcane Plant Seeds, Soaking Time, ZPT Atonic Solution